Recent turbulence in emerging capital markets : lessons for financial policy. - MONTGOMERY, John D. (1996)
Provides an overview of the conclusions of the IMF's 1995 capital markets report which looked at the events surrounding Mexico's devaluation and subsequent floating of the peso in December 1994, and the ensuing turbulence in Mexican and other markets. Focuses on policy toward financial markets issues.